How to Improve Patient Handoff Quality for Ensuring Patient Safety: A Systematic Review - Maharani, R; Thabrany, H (KnE Life Sciences, 2018)
Patient handoff is defined as a transfer and acceptance of responsibility for patient care that is achieved through effective communication. Communication breakdown in handoff procedures can lead to serious impacts in the patient’s care, inappropriate treatment, and potential harm to the patient. The aim of this systematic review is to know barriers in handoff process and find strategies to improve patient handoff quality for ensuring patient safety. The current study is systemic review with PRISMA method, retrieved from online databases such as ProQuest and PubMed using keywords ‘patient handoff’ OR ‘patient handover’ AND ‘patient safety’. The period of the study that has been reviewed is three years backwards. Based on this review, potential barriers that can lead to handoff failure are lack of standardized handoff tool, lack of chances for face-to-face communication and the ability to interactive discussion, and lack of staff training and handoff supervision. Several improvement strategies to increase patient handoff quality based on this review are: implementation of standardized verbal and written handoff protocols, face-to-face interaction with active discussion opportunities, minimal interruptions, accurate and up-to-date information with critical issues highlighted, staff education and training, handoff process supervision, leadership and regulation support. Improvements or impacts on patient safety were only stated in three journals. Barriers in handoff process must be addressed to find recommendation for handoff process improvement. By addressing barriers, patient handoff quality can be increased by several improvement strategies. Further studies are needed to prove the impact of effective patient handoff in reducing sentinel and adverse events. Keywords: patient handoff, patient safety, handoff barrier